2023
DOI: 10.3390/batteries9060301
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Modeling of Lithium-Ion Battery: Physics-Informed Neural Network for Battery State Estimation

Soumya Singh,
Yvonne Eboumbou Ebongue,
Shahed Rezaei
et al.

Abstract: Accurate forecasting of the lifetime and degradation mechanisms of lithium-ion batteries is crucial for their optimization, management, and safety while preventing latent failures. However, the typical state estimations are challenging due to complex and dynamic cell parameters and wide variations in usage conditions. Physics-based models need a tradeoff between accuracy and complexity due to vast parameter requirements, while machine-learning models require large training datasets and may fail when generalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Ensuring the robustness of DL models against uncertainties such as sensor noise, operational variations, and environmental changes remains a challenging task in BPHM [129]. Physics-informed neural networks combine physical laws with data-driven insights to provide comprehensive and reliable BPHM [130]. With LIB data scarcity, physics-guided DL can conserve a high performance of DL algorithms under unseen conditions [70].…”
Section: A Research Challengesmentioning
confidence: 99%
“…Ensuring the robustness of DL models against uncertainties such as sensor noise, operational variations, and environmental changes remains a challenging task in BPHM [129]. Physics-informed neural networks combine physical laws with data-driven insights to provide comprehensive and reliable BPHM [130]. With LIB data scarcity, physics-guided DL can conserve a high performance of DL algorithms under unseen conditions [70].…”
Section: A Research Challengesmentioning
confidence: 99%
“…Just in the past few months, scholars have extensively attempted to use PINN to solve PDE in their own industry field. Roh et al (2023) have attempted to use PINN to solve PDE in salinity transfer kinetics, and have demonstrated that this method has lower absolute deviation than ordinary artificial neural network (ANN) [61]; Singh et al (2023) have integrated particle models into the training process of NN, and have used PINN to predict the charging state and health state of lithium-ion batteries for PDE [62]; Zhou et al ( 2023) have even combined PINN with traditional FEM and have proposed an integrated smooth finite element method (SFEM) to solve elastic-plastic forward and inverse PDEs, which have achieved lower error [63].…”
Section: Solving Pdes Based On Pinnmentioning
confidence: 99%
“…There are also relevant studies using PINN [25][26][27][28] in the field of batteries. Li et al [25] used 2d-LSTM to build a state observer for the key parameters for the P2D model.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [28] utilized physics-informed neural networks as a solver for the PDE of lithium-ion concentration diffusion in electrode particles. The established battery model was then used to estimate the battery's state-of-charge (SOC) and state-of-health (SOH).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation